An Autonomous Cannabinoid System in Islets of Langerhans - Aseer, Kanikkai Raja; Egan, Josephine M. (Frontiers in Endocrinology, 2021)
While endocannabinoids (ECs) and cannabis were primarily studied for their nervous system effects, it is now clear that ECs are also produced in the periphery where they regulate several physiological processes, including energy storage, glucose and lipid metabolism, insulin secretion and synthesis, and hepatocyte function. Within islet of Langerhans there is an autonomous EC system (ECS). Beta (β)-cells contain all the enzymes necessary for EC synthesis and degradation; ECs are generated in response to cellular depolarization; their paracrine influence on β-cells is mostly through the cannabinoid 1 receptor (CB1R) that is present on all β-cells; they modulate basal and glucose- and incretin-induced insulin secretion, and β cell responses to various stressors. Furthermore, there is now accumulating evidence from preclinical studies that the autonomous islet ECS is a key player in obesity-induced inflammation in islets, and β-cell damage and apoptosis from many causes can be mitigated by CB1R blockers. We will thoroughly review the literature relevant to the effects of ECs and their receptors on β-cells and the other cell types within islets. Therapeutic potential of agents targeting EC/CB1R and CB2R is highly relevant because the receptors belong to the druggable G protein-coupled receptor superfamily. Present research in the ECS must be considered preliminary, especially with regards to human islet physiology, and further research is needed in order to translate basic cellular findings into clinical practice and the use of safe, clinically approved CBR modulators with and without glucose lowering combinations presently in therapeutic use for diabetes and obesity needs to be studied.